2009
DOI: 10.1017/s0967199408005133
|View full text |Cite
|
Sign up to set email alerts
|

The developmental potential of mouse somatic cell nuclear-transferred oocytes treated with trichostatin A and 5-aza-2′-deoxycytidine

Abstract: To facilitate nuclear reprogramming, somatic cells or somatic cell nuclear-transferred (SCNT) oocytes have been treated with the histone deacetylase inhibitor trichostatin A (TSA), or the DNA methyltransferase inhibitor, 5-aza-2'-deoxycytidine (5-aza-dC), to relax epigenetic marks of differentiated somatic cells. TSA-treated SCNT oocytes have increased developmental potential, but the optimal treatment period is unknown. Reduced methylation levels in somatic cells have no positive effect on SCNT oocytes, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 28 publications
3
51
0
1
Order By: Relevance
“…This is a necessary part of genetic reprogramming [86]. In fact, several reports clearly showed that HDACi treatment during SCNT cloning improved histone acetylation [87], nascent mRNA production [64] and gene expression [88] in a manner similar to that in normally fertilized embryos. TSA treatment also improved the long-term consistency of genome-wide gene expression regulation: the total number of genes commonly exhibiting up-or downregulation in the TSA-treated clone pups decreased to half of the conventional SCNT pups and the total gene expression profile of the TSA clones came to resemble that of the intracytoplasmic sperm injection (ICSI) pups [89].…”
Section: Technical Improvements Based On Histone Modificationsmentioning
confidence: 94%
“…This is a necessary part of genetic reprogramming [86]. In fact, several reports clearly showed that HDACi treatment during SCNT cloning improved histone acetylation [87], nascent mRNA production [64] and gene expression [88] in a manner similar to that in normally fertilized embryos. TSA treatment also improved the long-term consistency of genome-wide gene expression regulation: the total number of genes commonly exhibiting up-or downregulation in the TSA-treated clone pups decreased to half of the conventional SCNT pups and the total gene expression profile of the TSA clones came to resemble that of the intracytoplasmic sperm injection (ICSI) pups [89].…”
Section: Technical Improvements Based On Histone Modificationsmentioning
confidence: 94%
“…Reprogramming the meiotic deacetylation process by inhibiting deacetylation with the potent and specific histone deacetylase inhibitor trichostatin A (TSA) has been effective for in vitro and in vivo cloning efficiency (Rybouchkin et al, 2006;Tsuji et al, 2009;Kishigami et al, 2006), but has not induced sufficiently dramatic improvement. Although the low efficiency of SCNT embryos appears to be due to insufficient reprogramming of the donor nucleus in the ooplasm, this has not been clarified and overcoming this insufficient reprogramming presents several challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The application of TSA treatment in SCNT has resulted in higher pre-implantation embryonic development in pigs [61], cattle [7] and rabbits [36]. Although the application of TSA has resulted in improvements in the murine SCNT program [18,44], the effect of TSA on SCNT is still an issue in some animal species [26,36,57] and many research groups have suggested that it has various harmful effects on the development of mammalian SCNT embryos [26,44,57]. In our experiment, we investigated the optimal duration of TSA exposure during the early reprogramming event in SCNT embryos.…”
Section: Discussionmentioning
confidence: 99%